THE LEARNING AN ALYTICS APPLICATION LEMO – RATIONALSAND FIRST RESULTS - Elkina, Margarita; Fortenbacher, Albrecht; Merceron, Agathe (International Journal of Computing, 2014)
LeMo is an open source application for learning analytics, which collects data about learners’ activities from different platforms. This article describes design principles of LeMo in the context of creating an efficient tool for learning analytics. Focus is on the LeMo system architecture, user path analysis employing algorithms of sequential pattern mining, and visualization of learners’ activities implemented in the current version. A case stud y shows first results.